Penerapan Good Governance dalam Pelayanan Elektronik Kartu Tanda Penduduk di Kecamatan Sukolilo Surabaya - Cahyadi, Arif; Soenarjanto, Bagoes (Universitas 17 Agustus 1945 Surabaya, 2019)
The principles of good governance is the government whether it is done in the government in the implementation of the public service. So this research aims to determine and analyze the value of the application of good governance and also knowing and analyzing yhe value of the quality of public service in the Sukolilo in Surabaya. The gathering data carried out by using interviews conducted with the head of the sie the government, as well as questionnaires in the spread of the Sukolilo in Surabaya with the amount of an informant for the 25 people who take care of the sevice E – ID cards, and also use techniques the observation of data – data obtained from the Sukolilo in Surabaya. The data analysis carried out in this study is the reduction of data to select the data according to the research, also the presentation of data with the present data that has been reduced and obtained from the Sukolilo, Surabaya, and also use techniques of pigeons gathered to conclude the data that has been reduced and is served. The results of this that the value of the implementation of the principle of good governance in the service of the E – ID cards in the Sukolilo of Surabaya was enough it’s fine with the value of approximately 21,6 and obtained also the results of this research that the value of the quality of service E – ID cards in the Sukolilo of Surabaya was enough it’s fine with the value of approximately 51.Keywords: good governance, the quality of public service